Fostering the Development of Greenfield Mining-related Transport Infrastructure through Project Financing - International Finance Corporation (World Bank, Washington, DC, 2013)
The purpose of this study is to serve as a guide on developing Greenfield transport infrastructure (rail and port) primarily used to support mining operations ('mining-related infrastructure'), through Public-Private Partnership (PPP) schemes and on a project finance basis. The focus is on key financing issues and considerations, as well as recommendations for governments and private-sector participants, specifically in the context of sub-Saharan Africa and similar regions. Over the past decade, the rapid economic growth in newly industrialized markets has fueled a strong demand for various commodities (such as iron, coal, bauxite and copper), with significant impact on their prices. The last ten years have seen an unprecedented rise in the price of mineral commodities worldwide. From the mid-2000s through the early 2010s, the world's largest mining companies embarked in the planning of numerous and often very large mining projects to satisfy what was seen as an ever growing double digit demand for minerals (iron ore, coal, bauxite, copper, etc). A number of these mining projects are located in frontier countries (e.g. Mongolia, Guinea, Afghanistan, Sierra Leone and Mozambique). This report explores the challenges and solutions associated with the development of Greenfield mining-related transport infrastructure through project financing in frontier countries, including as shared-use assets. From an ownership and financing structure perspective, there are three traditional forms of ownership models: public-sector led, mining company-led or third-party investment. Given that most frontier host governments simply do not have the ability to fund these infrastructure projects on a purely public basis (including with the assistance of multilateral development banks), this report focuses on the latter two ownership arrangements. In terms of financing models, the size of such investments often rules out corporate financing as a viable option for external investors. Thus project financing is the most feasible and most adapted form of debt financing for Greenfield multi-user/multi-client mining-related infrastructure, assuming project bankability can be demonstrated to lenders. Lastly, public authorities might have to accept that multi-usage demands made to transport mining infrastructure operators might have to be initially or permanently restricted to secure, first and foremost, the delivery of an efficient mining transport system at the lowest possible cost to its anchor user/client.